2011
DOI: 10.1029/2011gc003630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sample pretreatment on the measured element concentrations in the bivalveArctica islandica

Abstract: [1] Correlating metal to calcium (Me/Ca) ratios of marine biogenic carbonates, such as bivalve shells, to environmental parameters has led to contradictory results. Biogenic carbonates represent complex composites of organic and inorganic phases. Some elements are incorporated preferentially into organic phases, and others are incorporated into inorganic phases. Chemical sample pretreatment to remove the organic matrix prior to trace element analysis may increase the applicability of the investigated proxy rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Importantly, recent work by Krause-Nehring et al (2011) demonstrates that treatment of biogenic carbonate with (31%) H 2 O 2 influences the elemental concentrations present. This is problematic for the interpretation of investigations concerning the chemical composition of biominerals that have been cleaned with H 2 O 2 .…”
Section: Elemental Analysis Of Clam Shellsmentioning
confidence: 97%
“…Importantly, recent work by Krause-Nehring et al (2011) demonstrates that treatment of biogenic carbonate with (31%) H 2 O 2 influences the elemental concentrations present. This is problematic for the interpretation of investigations concerning the chemical composition of biominerals that have been cleaned with H 2 O 2 .…”
Section: Elemental Analysis Of Clam Shellsmentioning
confidence: 97%
“…tion in coral cores (Nategaal et al, 2012). Krause-Nehring et al (2011) performed their study on powdered, pre-cleaned shells (manual removal of the periostracum) and found very little effect. In our study, where intact shells were pretreated with NaOCl, we suggest that the geochemical and crystallographic composition of the bivalves studied here was not significantly altered despite having some hypochlorite solution percolate through.…”
Section: Sample Preparationmentioning
confidence: 99%
“…According to Krause-Nehring et al (2011), the treatment of biogenic calcium carbonate to remove organic matter may have an impact on the elemental and crystallographic composition in the bivalve Arctica islandica. The effects of sodium hypochlorite (NaOCl) pretreatment (also used in our study) on A. islandica shell powder were insignificant compared to other treatments tested in that study.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The efficiency of this approach, however, remains questionable and chemical treatment itself may alter the outcome of subsequent Me/Ca analysis (Love and Woronow, 1991). Thus, we first examine the efficiency of eight chemical treatments and their impact on the carbonate composition (for further details see Krause-Nehring et al (2011)) (Effect of sample preparation).…”
Section: Introductionmentioning
confidence: 99%